Determinants of recovery from post-COVID-19 dyspnoea: analysis of UK prospective cohorts of hospitalised COVID-19 patients and community-based controls - Zheng, B; Vivaldi, G; Daines, L; Leavy, OC; Richardson, M; Elneima, O; McAuley, HJC; Shikotra, A; Singapuri, A; Sereno, M; Saunders, RM; Harris, VC; et al. (Elsevier, 2023)
Background The risk factors for recovery from COVID-19 dyspnoea are poorly understood. We investigated determinants of recovery from dyspnoea in adults with COVID-19 and compared these to determinants of recovery from non-COVID-19 dyspnoea.